Penggunaan Flash Card Sebagai Media Pembelajaran Kreatif Untuk Anak Berkebutuhan Khusus - Rida Rizkia Sari; Arini Lutfi Priandini; Moch. Ardan Aulia Fuzianto (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Education is a very important foundation that every human must have, with thegoal off or minga virtuous, virtuous human being, and certainly is brightening the life of the nation. A teacher and a learner certainly need learning media that meet the need. The learning media used for special needs children should be more interesting than ever. Professional teachers must be creative and innovative one of them in designing and creating a learning media. The essence of learning media is a crucial point to be conveyed to inherent learners from the syllabus, which is planning, purpose, prediction, and performance in the learning activity. In the development of this module the writer focuses on children's special needs the slow learner. Flash card media for the special needs of the slow learner is certainly provided by referencing teachers. Because in application there needs to be conditioning students in using the media. Many benefits derived from the use of flashcard.